THE HISTORICAL DEVELOPMENT OF APPLIED LINGUISTICS AS AN INDEPENDENT SCINCE IN CHINA FROM 1978 UP TILL NOWDAYS - Hunko, Liubov (Studies in Comparative Education, 2017)
The article describes the historical development of Applied Linguistics as an independent science in China from 1978 up till nowadays. It was the period when great changes and reforms happened in the Chinese science after years of stagnation. During this time a lot of researches on Applied Linguistics were developed, new approaches were integrated; great attention was payed to the correction of the mistakes of the past years and to the creation of a new theoretical base, which can match the requirements of the world standards. The author highlighted the key events in the process of the formation and development of Applied Linguistics in China, such as: opening training direction for master degree on the major «Linguistics and Applied Linguistics» in Guangzhou University of Foreign Studies (广州外国语学院); beginning first time in the whole country eight months course «The course of Applied Linguistics»; foundation of the «National Key Research Centre for Linguistics and Applied Linguistics» and publication of the journal «Applied Linguistics»(《语言文字应用》), one of the most important events of this period. The author researched the studies of the leading linguists in China, such as Dong Changlai (栋昌来)), Feng Zhiwei (冯志伟), Gui Shichun (桂诗春), Liu Yanchun (刘艳春), Shi Linping (石林平), Yu Genyuan (于根元), Wen Qiufang(文秋芳)), Zhang Yan (张艳) and others and on the base of this information created her own system of the historical development of Applied Linguistics in China. The successful experience of Applied Linguistics formation and development in Chine can be useful for the reformation of the major «Foreign language and Applied Linguistics» in Ukraine.